Sleep duration and eating behaviours in youth: a scoping review protocol - Mark A Ferro; Natalie Doan (BMJ Open)
Introduction Developmental alterations to the circadian rhythm, in combination with lifestyle changes (eg, changes in school start time, part-time employment), contribute to insufficient sleep among youth. Insufficient sleep is associated with poor eating behaviours in other developmental stages (ie, childhood, adulthood); however, it is currently unknown if this finding generalises to youth. Consequently, identifying the characteristics and results of the studies examining this relationship in youth populations is necessary to guide the future direction of research in this field.Methods and analysis We will conduct a scoping review to investigate the literature examining the relationship between sleep duration and eating behaviours in youth. The proposed scoping review will follow the standard six-stage protocol outlined by Arksey and O’Malley. To acquire relevant publications, systematic searches were conducted in PubMed, CINHAL, PsycINFO and Scopus in August 2019. Following this, a scan of the grey literature will be conducted. All relevant publications will be screened for their eligibility based on the predefined inclusion and exclusion criteria. A data extraction tool will be used to collate, summarise and report the results. The findings of the scoping review will be reviewed by relevant stakeholders to aid in interpreting and disseminating the findings. The proposed review will identify existing gaps in the literature and inform the conduct of future studies aimed at understanding the effects of insufficient/excessive sleep and the eating behaviours of youth.Ethics and dissemination This scoping review does not require ethics approval. Following the completion of the study, the findings will be disseminated at scientific meetings, submitted for peer-reviewed publication and translated to an accessible format for other relevant stakeholders.